India : Can We Make Parenting Programs More Cost-Effective? - World Bank (World Bank, Washington, DC, 2021)
In the first years of life, all children need healthy food, a clean environment, and stimulation to thrive and reach their full developmental potential. However, poverty prevents millions of young children in low- and middle-income countries from receiving adequate nutrition and stimulation. As a result, many disadvantaged children’s brain development lags behind that of their well-off peers, which can have lifelong consequences. Previous research from low-income settings has found that encouraging parents to play and interact more with their children can improve children’s brain development, with impacts that can last into adulthood. Delivering these parenting programs at scale and in a cost-effective manner, however, has been a challenge, in part because some of the most successful programs have been delivered through intensive and relatively costly home-based programs.